Distribution and chronology of Pleistocene permafrost features in France: Database and first results. (4th June 2013) - Bertran, Pascal; Andrieux, Eric; Antoine, Pierre; Coutard, Sylvie; Deschodt, Laurent; Gardère, Philippe; Hernandez, Marion; Legentil, Claude; Lenoble, Arnaud; Liard, Morgane; Mercier, Norbert; Moine, Olivier; et al.
<x xml:space="preserve">Abstract</x> Numerous periglacial features (polygons, nets, soil stripes, ice‐wedge pseudomorphs and sand‐wedge casts, involutions) have been recorded in France by examining bibliographical sources and aerial photographs. These data show that a large part of France was affected by permafrost during the Pleistocene and only the southern Aquitaine Basin and Languedoc seem to have been beyond its maximum extent. The first OSL ages obtained from the aeolian infill of wedge structures indicate that at least two phases of thermal contraction cracking occurred in southwestern France between ∼25 and 36 ka. Chronostratigraphical data from loess in northern France indicate that these episodes correspond to the formation of ice‐wedge networks associated with tundra gleys. In the latter region, two additional permafrost episodes probably occurred during the Last Glacial, the older one corresponding to the end of Marine Isotope Stage (MIS) 4 around 60 ka and the more recent one to MIS 2 around 19–16 ka. Although stratigraphical data indicate that these episodes were relatively short (about one millennium), relict permafrost may have existed for longer periods in northern France.